Dendritic Architecture Predicts in vivo Firing Pattern in Mouse Ventral Tegmental Area and Substantia Nigra Dopaminergic Neurons - Montero, Trinidad; Gatica, Rafael Ignacio; Farassat, Navid; Meza, Rodrigo; González-Cabrera, Cristian; Roeper, Jochen; Henny, Pablo (Frontiers in Neural Circuits, 2021)
Firing activity of ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) dopaminergic (DA) neurons is an important factor in shaping DA release and its role in motivated behavior. Dendrites in DA neurons are the main postsynaptic compartment and, along with cell body and axon initial segment, contribute to action potentials generation and firing pattern. In this work, the organization of the dendritic domain in individual VTA and SNc DA neurons of the adult male mouse, and their relation to in vivo spontaneous firing, are described. In comparison to dorsal VTA DA neurons, ventrally located VTA neurons (as measured by cell body location), possess a smaller total dendritic length and simpler dendritic architecture, and exhibited the most irregular in vivo firing patterns among DA neurons. In contrast, for DA neurons in the SNc higher irregularity of firing related to a smaller dendritic domain, as measured by convex hull volumes. However, firing properties were also related to specific regional distribution of the dendritic tree. Thus, VTA DA neurons with larger extension of their dendritic tree within the parabrachial pigmented nucleus (PBP) fired more regularly compared to those with relatively more dendrites extending outside the PBP. For DA neurons in the SNc, enhanced firing irregularity was associated with a smaller proportion of dendrites penetrating the substantia nigra pars reticulata. These results suggest that differences in dendritic morphology contribute to the in vivo firing properties of individual DA neurons and the existence of region-specific synaptic connectivity rules that shape firing diversity.